The effect of 'cytochrome P-450 2C9' and 'vitamin K epoxide reductase complex 1' genetic polymorphism upon oral anticoagulation requirements - Hossam Y.K Mohammed; Yousry Z Al-Zohairy; Mahmoud Abd El-Latif Hashish (Wolters Kluwer Medknow Publications, 2018)
Background Polymorphisms in the gene encoding the cytochrome P-450 2C9 enzyme (CYP2C9) are known to contribute to variability in sensitivity to Marevan. CYP2C9 is the enzyme primarily responsible for the metabolic clearance of s-enantiomer of Marevan. The vitamin K epoxide reductase complex 1 (VKORC1) is the target of coumarin anticoagulants, and its common genetic variants result in altered sensitivity to Marevan. VKORC1 polymorphisms are associated with a need for lower doses of Marevan during long-term therapy. Aim of work This study aimed to assess the allelic frequencies and to investigate the relationship between 'CYP2C9' and 'VKORC1' genotype and vitamin K antagonist anticoagulation. Patients and methods This study was conducted on 40 patients. There were 24 females and 16 males, with a male to female ratio of 2 : 3. Their ages ranged from 28 to 72 years. All the studied patients were laboratory investigated with international normalized ratio, complete blood count, and detection of VKORC1 and CYP2C9 by PCR reverse hybridization method using PGX thrombo strip assay (Vienna Lab.). Results Regarding the distribution of patients according to frequency of deep venous thrombosis (DVT) attacks, 16 (40%) patients showed single attack of DVT and 24 (60%) patients showed recurrent attacks. Patients with single attack of DVT comprised 12 (75%) females and four (25%) males, with male to female ratio of 1 : 3. As for the patients with recurrent attacks of DVT, there were 13 (54.2%) female and 11(45.8%) male patients, with a male to female ratio of 1 : 1.2. Conclusion Detection of genetic polymorphisms in CYP2C9 and VKORC1 genes before onset of warfarin therapy greatly influenced response to warfarin and shortened the time required to reach target international normalized ratio, and hence reduced the risk of recurrence of DVT.